2018
DOI: 10.20546/ijcrar.2018.608.010
|View full text |Cite
|
Sign up to set email alerts
|

Management of Turcicum Leaf Blight (Exserohilum turcicum) of Maize (Zea mays) through Evaluation of Maize Varieties and Fungicide Spray Frequencies at Ambo, Ethiopia

Abstract: Article InfoTurcicum leaf blight (Exserohilum turcicum), TLB, is a major disease affecting maize (Zea mays) in western Ethiopia. The aims of this study wereto: evaluate maize varieties and propiconazole spray frequencies on epidemics of TLB, determine optimum propiconazole (tilt 250 EC) spray frequency for integrated management of TLB, and assess the cost/benefit of using propiconazole for each spray frequency against TLB. The effects of maize varieties, fungicide frequencies and their interactions on TLB deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In addition to periodic changes in the weather, changes in the host-pathogen genetic interrelationship may also be induced by the introduction of new cultivars or the occurrence of mutations and recombination in the pathogen, which influences the epidemic development of the diseases. Tajudin et al (2018) reported that the TLB progression rate ranged between 0.016 and 0.093 unit day −1 . Additionally, Megersa et al (2017) reported that the highest TLB progression rate was recorded in the variety BH-543 (0.041 unit day −1 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to periodic changes in the weather, changes in the host-pathogen genetic interrelationship may also be induced by the introduction of new cultivars or the occurrence of mutations and recombination in the pathogen, which influences the epidemic development of the diseases. Tajudin et al (2018) reported that the TLB progression rate ranged between 0.016 and 0.093 unit day −1 . Additionally, Megersa et al (2017) reported that the highest TLB progression rate was recorded in the variety BH-543 (0.041 unit day −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tajudin et al. (2018) indicated that TLB on maize reduced the NEPP, ear size (length), and NRPE, while checking TLB development with propiconazole, especially with three application frequencies, significantly increased these yield parameters. A significant increase in plant height was noticed in fungicide‐protected plots over unprotected plots.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations